The Union Cavalry in the Civil War / From Fort Summer to Gettysburg 1861-1863; Volume I - Starr Stephen Z (Louisiana State University Press, 1979)
Preface, Introduction: Climax in Alabama, Prelude to War, The Noise of the Captains, Assume the Port of Mars, Arms and the Man, Officers and Gentlemen, Gone for a Soldier, To the Tented Field, Jine the Cavaltry, Prepare to Mount, Who Ever Saw a Dead Cavalryman?, A Noise of Horses, The Edge of the Sword, The Divide, Their Arms Flash in the Sun, Cold Steel, Solstice, A River to Cross, Appendix, Bibliography, Index.
Preface, Introduction: Climax in Alabama, Prelude to War, The Noise of the Captains, Assume the Port of Mars, Arms and the Man, Officers and Gentlemen, Gone for a Soldier, To the Tented Field, Jine the Cavaltry, Prepare to Mount, Who Ever Saw a Dead Cavalryman?, A Noise of Horses, The Edge of the Sword, The Divide, Their Arms Flash in the Sun, Cold Steel, Solstice, A River to Cross, Appendix, Bibliography, Index.